Assessing the diversification risk of a single equity market: Evidence from the largest European stock indexes - Artor Nuhiu; Florin Aliu; Bedri Peci (International Journal of Management and Economics, 2022)
Diversification of financial securities is considered a substantial element of portfolio risk. In this context, the construction of an optimal portfolio is an ongoing concern for portfolio managers. This study measures the risk-reward tradeoffs linked to the stock indexes of Germany, Spain, Italy, France, and England. First, the stock indexes are analyzed as individual portfolios and later compared to the hypothetical common equity index. The results show diversification benefits gained from a hypothetical common European stock market. Individual stock prices and trade volumes are collected weekly from January 1, 2008 to December 31, 2018. The results indicate that, on average, the most well-diversified equity indexes are IBEX35, FTSE MIB, and FTSE100. In contrast, DAX, MDAX, and CAC40 on average tend to be less diversified. The diversification risk for DAX, MDAX, and CAC40 decreases from joining a common hypothetical stock market, while for FTSE100, FTSE MIB, and IBEX it increases.
Keywords: G11; G15; 650; diversification benefits; financial crisis; risk perspective; single equity market; stock index